Breeding for High Oleate Oilseed Crops: Opportunities, Constraints, and Prospects - Gangurde, Sunil S.; Bhat, Ramesh S.; Shirasawa, Kenta; Varshney, Rajeev K.; Pandey, Manish K. (Springer, 2025)
Breeding for high oleate oilseed crops for healthier and more stable oils has seen significant progress over the years. This review explores the fatty acid composition of plant oils, emphasizing the shift toward higher oleic acid content. It highlights various alternative oilseeds, including soybean, rapeseed, sunflower, peanut, etc., as promising candidates for breeding programs. Factors influencing fatty acid composition, such as environmental conditions and genetic factors, are examined in detail. Key enzymes and genes regulating fatty acid biosynthesis, particularly stearoyl-ACP desaturase (SAD) and fatty acid desaturase (FAD), are discussed for their pivotal roles in determining oleate levels. Advances in gene discovery have identified crucial genetic determinants that facilitate targeted breeding for high oleate traits. Traditional breeding techniques are complemented by marker-assisted breeding, enhancing the precision and efficiency of developing high oleate cultivars. Genetic engineering and gene editing technologies, such as CRISPR/Cas9, offer transformative prospects for modifying fatty acid biosynthesis pathways. These cutting-edge approaches enable the precise manipulation of SAD and FAD genes to achieve desired fatty acid profiles. This review underscores the successful development of several improved varieties across various crops, reflecting the tangible outcomes of these advancements.